2022
DOI: 10.3390/su14010488
|View full text |Cite
|
Sign up to set email alerts
|

Positive Organizational Practices, Life Satisfaction, and Psychological Capital in the Public and Private Sectors

Abstract: Public and private sector employees confronted stressful life circumstances that affected the world during the COVID-19 pandemic. Therefore, new knowledge on possible psychological and organizational resources is needed. This study aimed to explore positive organizational practices, psychological capital, and life satisfaction of employees in the public and private sectors. The survey applied the Satisfaction with Life Scale (SWLS), the Psychological Capital Questionnaire—PCQ-24, validated in the Lithuanian po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 196 publications
0
4
0
Order By: Relevance
“…In addition, it aimed to assess whether mindfulness, psychological capital, and life satisfaction are linked to different leisure preferences. Many previous studies established links between leisure preferences and life satisfaction [ 23 , 31 ], links between life satisfaction and psychological capital [ 89 , 90 , 125 , 126 , 127 , 128 ], life satisfaction and mindfulness [ 129 , 130 ], or mindfulness and psychological capital [ 72 , 74 , 76 , 131 ]. Previous studies also examined links between several types of leisure activities and psychological capital [ 99 , 132 ] or links between some activities (meditation, physical activity) and mindfulness [ 9 , 133 , 134 , 135 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it aimed to assess whether mindfulness, psychological capital, and life satisfaction are linked to different leisure preferences. Many previous studies established links between leisure preferences and life satisfaction [ 23 , 31 ], links between life satisfaction and psychological capital [ 89 , 90 , 125 , 126 , 127 , 128 ], life satisfaction and mindfulness [ 129 , 130 ], or mindfulness and psychological capital [ 72 , 74 , 76 , 131 ]. Previous studies also examined links between several types of leisure activities and psychological capital [ 99 , 132 ] or links between some activities (meditation, physical activity) and mindfulness [ 9 , 133 , 134 , 135 ].…”
Section: Discussionmentioning
confidence: 99%
“…It can be argued that people with high levels of LS are more likely to navigate cumulative and unpredictable changes in work more successfully. The positive significant link between life satisfaction and organizational resilience highlights the interdependence between individual well-being and organizational success [75]. The adaptive capacity of an organization, a key component of resilience, is positively influenced by satisfied and motivated employees [76].…”
Section: Psychological Resilience Life Satisfaction and Organizationa...mentioning
confidence: 99%
“…The authors of PsyCap (Youssef-Morgan and Luthans, 2015) referred to these four mechanisms as the "HERO within" (Hope, Efficacy, Resilience, and Optimism), claiming they act as a single body in facilitating the various positive and negative experiences of individuals. PsyCap as a personal construct has gained significant attention from scholars in various fields, including organizational and management (Liu, 2021;Dirzyte and Patapas, 2022). Research showed that PsyCap could be relevant for many job-related outcomes, such as job satisfaction (Zhang et al, 2021), innovation (Dimas et al, 2022), and problemsolving (Ho and Chan, 2022), as well as health performance, such as reducing emotional exhaustion (Jung and Yoon, 2022) and increasing overall mental health (Cao et al, 2022).…”
Section: Psycap Profiles and Lmx As A Predictor Of Their Transitionmentioning
confidence: 99%
“…PsyCap as a personal construct has gained significant attention from scholars in various fields, including organizational and management ( Liu, 2021 ; Dirzyte and Patapas, 2022 ). Research showed that PsyCap could be relevant for many job-related outcomes, such as job satisfaction ( Zhang et al, 2021 ), innovation ( Dimas et al, 2022 ), and problem-solving ( Ho and Chan, 2022 ), as well as health performance, such as reducing emotional exhaustion ( Jung and Yoon, 2022 ) and increasing overall mental health ( Cao et al, 2022 ).…”
Section: An Applied Examplementioning
confidence: 99%